2016
DOI: 10.1245/s10434-016-5558-8
|View full text |Cite
|
Sign up to set email alerts
|

Postmastectomy Radiotherapy: An American Society of Clinical Oncology, American Society for Radiation Oncology, and Society of Surgical Oncology Focused Guideline Update

Abstract: PurposeA joint American Society of Clinical Oncology, American Society for Radiation Oncology, and Society of Surgical Oncology panel convened to develop a focused update of the American Society of Clinical Oncology guideline concerning use of postmastectomy radiotherapy (PMRT).MethodsA recent systematic literature review by Cancer Care Ontario provided the primary evidentiary basis. The joint panel also reviewed targeted literature searches to identify new, potentially practice-changing data.RecommendationsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 72 publications
1
86
1
2
Order By: Relevance
“…Current guidelines 7 recommend strong consideration of PMRT to the chest wall and regional lymph nodes for patients who undergo mastectomy with 1 to 3 positive nodes, but whether micrometastases contribute to the positive node count is uncertain. 23 In our study, we found no difference in LRR with or without PMRT by Kaplan-Meier estimation (p = 0.4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current guidelines 7 recommend strong consideration of PMRT to the chest wall and regional lymph nodes for patients who undergo mastectomy with 1 to 3 positive nodes, but whether micrometastases contribute to the positive node count is uncertain. 23 In our study, we found no difference in LRR with or without PMRT by Kaplan-Meier estimation (p = 0.4).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the vast majority of patients did not receive PMRT, and rates of LRR in this group were less than 5%, far lower than the rates of LRR in the no-radiotherapy arms of the clinical trials that suggested a benefit for PMRT in patients with 1–3 nodal metastases. 7,24 The 10-year results of the MA.20 and EORTC trials showed decreased LRR and improved disease-free survival with comprehensive nodal irradiation in patients with T1–T3, node-positive or ‘high-risk’ node-negative disease. The majority of patients underwent breast conservation, and micrometastases were not analyzed separately; the improvement in locoregional control was attributed in part to a decrease in internal mammary recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first automated treatment planning tool designed for PMRT, which uses tangential fields to irradiate the chest wall matched with an oblique en face beam to irradiate the SCV lymph nodes. Although some clinics may also include the internal mammary chain (IMC) lymph nodes in such treatment, this remains an area of controversy . Treatment of the IMC increases the dose delivered to the heart and the risk of heart disease .…”
Section: Discussionmentioning
confidence: 99%
“…A key question is whether spending variation is appropriate or inappropriate. Appropriate spending variation may be driven by unobservable patient preferences, such as when there is choice between breast‐conserving surgery and mastectomy, or clinical uncertainty, such as at the end‐of‐life when there is the least evidence to guide decision‐making . Other clinical factors, such as whether patients have a BRCA mutation or whether the cancer disease progresses/recurs soon after initial diagnosis, are unobservable in our data and may also lead to appropriate differences in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%